STIE Mahardika PENGARUH DIGITAL MARKETING DAN ADVERTISING TERHADAP PENJUALAN VESPA MATIC DI INSTAGRAM - Baidhowi, Achmad; Yusuf, Mochammad alfin Solikhin; Alfattakhy, Moch Zakhy; Kusmayati, Nindya Kartika (Politeknik Bisnis Indonesia, 2025)
Information technology has changed marketing strategies in many industries, including the automotive industry. The purpose of this study is to evaluate the effect of advertising and digital marketing on increasing Vespa Matic sales through the Instagram platform. Quantitative research with multiple linear regression was used. Data from 44 respondents were tested partially (t-test) and simultaneously (F-test). The results showed that advertising and digital marketing contributed positively and significantly to increasing sales. According to the regression coefficient value, a 1% increase in digital marketing has the potential to increase sales by 0.476, while a 1% increase in advertising strategy has the potential to increase sales by 0.500. These results indicate that social media, especially Instagram, functions as an effective digital promotion tool in increasing market reach and driving purchasing decisions, especially among the millennial generation. To increase market appeal and reach, the Vespa Matic brand must continue to optimize the use of digital media, especially Instagram, by presenting promotional content that is attractive, informative, and in accordance with the demographics of millennial customers. Promotional strategies such as discounts, bundling, and collaboration with influencers must be maximized.